Nilai Kesetiaan dalam Elong Ugi Assimellereng (Kajian Semiotika Ferdinand De Saussure) serta Relevansinya Terhadap Pembelajaran Bahasa dan Sastra Daerah Bugis - Henny Alfiana; Andi Agussalim; Hajrah Hajrah (SOCIETIES: Journal of Social Sciences and Humanities, 2022)
Abstract. Penelitian The background of this research is that the composition of loyalty within the scope of social life has not yet been achieved, so that there is still someone in their social interactions who have a lack of self-confidence, hopelessness and divorce can occur. Instilling loyalty in a person by following the times can be through literary works created through the imagination of authors who are motivated by facts in social life. One form of literary work that can be used as an inculcation of the value of loyalty is Elong. One form of this type of literary work has an appeal because its content uses local poetic languages so that it can convey messages in a unique way. This research is a type of qualitative research that examines the value of loyalty in Elong Ugi Assimellereng by using a semiotic approach and its relevance in learning the language and literature of the Bugis region. The data source uses primary data with reading and note-taking techniques which are analyzed using the semiotics of markers and signifiers Ferdinand De Saussure. The results of this study indicate that 1) the value of loyalty in Elong Ugi Assimellereng, namely there are 18 Elong verses that show the value of loyalty to promises and to self. 2) Elong Ugi has relevance to the folklore course (oral literature) with learning materials for rhymes and folk poetry, folk prose stories (Mite, Legend and fairy tales) Keywords: Loyalty, Elong Ugi Assimellereng, Semiotics, learning